Proses Analisis Jabatan Dan Analisis Beban Kerja (Studi Pada Biro Organisasi Sekretariat Daerah Jawa Timur) - Evolisa, Esti Ebhi (Jurnal Administrasi Publik, 2015)
Abstract: Process of Occupation Analysis and Workload Analysis (Study On The Organization Of The Bureau The Secretariat Of East Java). The Constitution of Repbulic Indonesia Number 5 Year 2014 about State Civil Apparatus Article (56) state that every government in stitution shouldarrange theam ount of need sand types of PNS’s occupation based on occupation analysis and workload analysis. Related to this case, we need arrange the occupation analysis based on the Regulation of the Minister of Internal Affairs of the Republic of Indonesia Number 35 Year 2012 about Occupation Analysis in Minister of Internal Affairs and Local Government and Workload Analysis based on the Regulation of the Minister of Internal Affairs Number 12 Year 2008 about The Guidance of Workload Analysis in Internal Affairs Department and Local Government. Resource Management Apparatus (MSDA) provide a description of that resource management becomes very important and at the moment the activity resource management apparatus will effectively increase the success of the Government's vision and mission. Process of occupation was using step of preparation, collecting data, data management, verification, completion, and result determination of occupation. Process of workload analysis was using step of collecting data, data management, review of the data, and result determination of workload analysis. Keyword: MSDA, occupation analysis, work load analysis.   Abstrak: Proses Analisis Jabatan Dan Analisis Beban Kerja (Studi Pada Biro Organisasi Sekretariat Daerah Jawa Timur). Undang-undang Republik Indonesia Nomor 5 Tahun 2014 Tentang Aparatur Sipil Negara Pasal (56) menyatakan bahwa setiap instansi Pemerintah wajib menyusun kebutuhan jumlah dan jenis jabatan PNS berdasarkan analisis jabatan dan analisis beban kerja. Berkaitan dengan hal tersebut perlu disusun analisis jabatan berdasarkan Peraturan Menteri Dalam Negeri Republik Indonesia No. 35 Tahun 2012 Tentang Analisis Jabatan Di Lingkungan Kementerian Dalam Negeri Dan Pemerintah Daerah dan analisis beban kerja berdasarkan Peraturan Menteri Dalam Negeri No. 12 Tahun 2008 Tentang Pedoman Analisis Beban Kerja Di Lingkungan Departemen Dalam Negeri Dan Pemerintah Daerah. Manajemen Sumberdaya Aparatur (MSDA) memberikan gambaran bahwa pengelolaan sumberdaya menjadi sangat penting dan pada saat ini aktivitas pengelolaan sumberdaya aparatur secara efektif akan meningkatkan keberhasilan visi dan misi pemerintah. Proses analisis jabatan melalui tahap persiapan, pengumpulan data, pengelolaan data, verifikasi, penyempurnaan, dan penetapan hasil analisis jabatan. Proses analisis beban kerja melalui tahap pengumpulan data, pengolahan data, penelaahan hasil olahan data, dan penetapan hasil beban kerja.   Kata Kunci: MSDA, analisis jabatan, analisis beban kerja.